PENGARUH OBJEKTIVITAS, PENGALAMAN KERJA, DAN INTEGRITAS TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI (Studi Pada Inspektorat Provinsi dan Kota di Riau) - Diven Kresnhadi Satra Pradana; Andreas -; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to see the effect of Effect of Objectivity, Work Experience and Integrity to Audit Quality with Auditor’s Ethic as Variable of Moderation. Research carried out on 3 working units i.e Inspectorate of Riau Province, Pekanbaru City and Dumai City on 2015. Sample used as respondens were taken by using proposive sampling method. Each population is represented by auditor and Supervisor of Government Business’s Organizer at region (P2UPD). Questionnaires were distributed to 74 respondents, and successfully reassembled with complete answers obtained from 65 respondents. Data were collected from 65 respondents further data were analyzed by using software of SPSS version 20.0 using descriptive statistical analysis and multiple linear regression analysis to generate the classical assumption, the model data analysis, coefficient of determination and prove the hypothesis. The results partially or simultaneously find that the variable of objectivity, work experience, integrity and auditor’s ethic as moderation effects the audit quality.Keywords: Objectivity, Work Experience, Integrity, Auditor’s Ethic, and Audit Quality